Study on the development of the DNS root system - Zhi-wei YAN; Guang-gang GENG; Hong-tao LI; Xiao-dong LI (网络与信息安全学报)
The development history of the DNS root system was described and the management of the DNS root service was explained in detail.Based on the shortcomings on efficiency,scalability and stability of the current DNS root server management model,the extension schemes from both policy and technology points of views were summarized and analyzed.